Gene conversion causing human inherited disease: Evidence for involvement of non-B-DNA-forming sequences and recombination-promoting motifs in DNA breakage and repair - Chuzhanova, Nadia; Chen, Jian-Min; Bacolla, Albino; Patrinos, George P; Férec, Claude; Wells, Robert D; Cooper, David N (Human mutation, 2009)
A variety of DNA sequence motifs including inverted repeats, minisatellites, and the χ recombination hotspot, have been reported in association with gene conversion in human genes causing inherited disease. However, no methodical statistically based analysis has been performed to formalize these observations. We have performed an in silico analysis of the DNA sequence tracts involved in 27 nonoverlapping gene conversion events in 19 different genes reported in the context of inherited disease. We found that gene conversion events tend to occur within (C+G)- and CpG-rich regions and that sequences with the potential to form non-B-DNA structures, and which may be involved in the generation of double-strand breaks that could, in turn, serve to promote gene conversion, occur disproportionately within maximal converted tracts and/or short flanking regions. Maximal converted tracts were also found to be enriched (P<0.01) in a truncated version of the χ-element (a TGGTGG motif), immunoglobulin heavy chain class switch repeats, translin target sites and several novel motifs including (or overlapping) the classical meiotic recombination hotspot, CCTCCCCT. Finally, gene conversions tend to occur in genomic regions that have the potential to fold into stable hairpin conformations. These findings support the concept that recombination-inducing motifs, in association with alternative DNA conformations, can promote recombination in the human genome. Hum Mutat 30:1-10, 2009.